(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article considers the main structural components and varieties of insults, which have a different language structure in exclamation and motivation. The author pays attention to the fact that the insult is the only investigated speech genre, directly related to verbal aggression. And also the article reveals the most common forms of insults to the addressee and their impact on him. Thus, the insult is an evaluative speech genre, the communicative goal of which is «to change the feelings of the participants in communication, correlating their actions, qualities and all other manifestations with the scale of values adopted in the society»